The Influence of Recruitment, Extrindic Rewards, and Training on Employee Performance in PT. Bakrie Metal Industries Bekasi - Widi Nugroho; beti nurbaiti (Journal of Accounting, Business and Management (JABM), 2023)
Specifically, this study aims to determine how much influence the recruitment of extrinsic reward and training on employee performance at PT. Bakrie Metal Industries simultaneously. The population is 344 employees and a sample of 125 employees is taken. The writer uses quantitative methods using Structural Equation Modeling (SEM) with the help of Lisrel 8.8 software (t value > 1.96) and primary data was obtained from questionnaires whose measurements used a Likert scale that was tested for validity and reliability. The results of the study based on the validity and reliability test showed that the data was valid and reliable. Based on the t test and F test shows that recruitment, extrinsic rewards and training have positive and significant effect on the performance of employees at PT Bakrie Metal Industries Bekasi.